Maine Libraries: A History of Sharing and Collaboration - Sanborn, James; Nutty, David (Maine Policy Review, 2013)
The high degree of collaboration among all types of Maine libraries is a unique and defining characteristic of the Maine library community. This article explores the history of sharing and cooperation among Maine’s libraries, identifies several ongoing collaborations and current projects, and explores some of the underlying factors that support this culture of collaboration. An argument is made for policies that would further collaboration through better coordination and funding of cooperative library activities.